SPATIAL ANALYSIS OF INCOME INEQUALITY IN INDONESIA - Gunawan, Diah Setyorini; Ahmad, Abdul Aziz; Gunawan, Ratna Setyawati (Jurnal REP (Riset Ekonomi Pembangunan), 2025)
This study seeks to analyze the spatial dimension of income inequality in Indonesia.  This study was conducted by comparing the spatial dimension of income inequality in Indonesia in 2019 with the spatial dimension of income inequality in Indonesia in 2024. This study can provide an overview of income inequality over the last 5 years, before the Covid-19 pandemic and after the recovery period from the impact of the Covid-19 pandemic. The similarities with previous research is found in the area of focus. Meanwhile, the differences lies on the analysis method used. The data used in this study is the value of Gini Ratio for 2019 period and 2024 period. Analysis method used includes geographic information system analysis and Moran index analysis.  The finding of this study is from the mapping with using geographic information system analysis, it can be seen that the provinces with the highest income inequality in 2019 period did not necessarily have high income inequality in 2024 period. Conversely, the provinces with the lowest income inequality in 2019 period did not necessarily have low income inequality in 2024 period.  The analysis result of Moran index in 2019 period and 2024 period indicated positive and significant value of Moran index.  Positive and significant value of Moran index meant that there were clustered areas which have the same characteristic. Policy implication of this study is that, collaboration across levels of government and a focus on strategic infrastructure, education, and improving the distribution of social assistance.